2012
DOI: 10.3109/00207454.2011.622453
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Artery Dissection: Risk Factors, Treatment, and Outcome; A 5-Year Experience From a Tertiary Care Center

Abstract: Hypertension and hypercholesterolemia were risk factors in spontaneous dissections, speaking for vascular wall abnormalities as potential contributors to pathophysiology of CAD. There was no evidence supporting one type of treatment over the other. A large ongoing prospective study should quell this controversy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 23 publications
0
24
0
5
Order By: Relevance
“…Several retrospective studies and a meta-analysis did not show any difference between stroke recurrence and bleeding complications between the two treatments. 48, 49 . While the mechanism of stroke in patients with cervical artery dissection is thought to be artery-to-artery embolism, it is unclear whether or not anticoagulation is the treatment of choice in this instance.…”
Section: Resultsmentioning
confidence: 99%
“…Several retrospective studies and a meta-analysis did not show any difference between stroke recurrence and bleeding complications between the two treatments. 48, 49 . While the mechanism of stroke in patients with cervical artery dissection is thought to be artery-to-artery embolism, it is unclear whether or not anticoagulation is the treatment of choice in this instance.…”
Section: Resultsmentioning
confidence: 99%
“…One study based on 5 years of data found that spontaneous dissections occurred more frequently in patients with preexisting hypertension. 25 Hemodynamic were also thought to be an etiological factor, which contributes to elastic lamina injury and subsequent aneurysm formation. Our result found that hypertension was associated with unfavorable outcome (P 5 .022), and we concluded that hypertension may be related with hemodynamic stress, which contributed to aneurysm rupture and affected the prognosis.…”
Section: Hypertension and Outcomementioning
confidence: 98%
“…5 No significant differences in the risk of death or ischemic stroke between anticoagulation and antiplatelet therapies have been shown, 11 and a 5-year study showed that patients on anticoagulation versus antiplatelet therapy fared equally well. 12 However, having no randomized trial to prove one more efficacious than the other leaves deciding on anticoagulation versus antiplatelet therapy to previous clinical experience and current clinical judgment.…”
Section: Discussionmentioning
confidence: 99%